A Survey of Selected School-Counselor Training Programs in Canadian Universities - Guttman, Mary A. Julius (Canadian Journal of Counselling and Psychotherapy, 2012)
A questionnaire was sent to various Canadian counselor educators and educational ministerial officials regarding the nature of training opportunities in counselor education in Canada. From the results of the questionnaire, 14 universities were identified as offering a master's degree in counseling. These training programs were compared on such variables as the requirements of the program, the structure and format of the training experiences, and the opportunities for counseling experience via practicum placements. Recommendations for improvements and development in counselor education training programs were discussed. Only Anglophone universities were included in the survey.